Évolution des rôles sociaux des traducteurs et son impact sur la recherche et sur la formation universitaire - Dzida-Błażejczyk, Monika; Tomaszkiewicz, Teresa (Studia Romanica Posnaniensia, 2024)
The article discusses the evolution of translator training through the experience of both a trainer and professional translator. It examines the historical and scientific perspectives of social roles and functions of translators. These serve as a starting point for analysing the current state of translation and its future. The profession of translation is currently in the process of change due to rapid technological and social advancements. The translators-to-be must possess new skills to adapt to these changes. To achieve this, universities should adapt their teaching methods and content to enable learners to cope with the new technical, social and communicational developments. These should equip translators-to-be with the necessary skills to meet the demands of today and tomorrow’s markets. Revision of the field history, past and contemporary research as well as practical professional experience provided in this article point to the training needs that must be fulfilled to meet the requirements of our time.